Improving accuracy and precision of ice core δD(CH 4 ) analyses using methane pre-pyrolysis and hydrogen post-pyrolysis trapping and subsequent chromatographic separation - Bock, Michael; Schmitt, Jochen; Beck, Jonas; Schneider, Robert; Fischer, Hubertus (Atmospheric Measurement Techniques, 2014)
Firn and polar ice cores offer the only direct palaeoatmospheric archive. Analyses of past greenhouse gas concentrations and their isotopic compositions in air bubbles in the ice can help to constrain changes in global biogeochemical cycles in the past. For the analysis of the hydrogen isotopic composition of methane (δD(CH4) or δ2H(CH4)) 0.5 to 1.5 kg of ice was hitherto used. Here we present a method to improve precision and reduce the sample amount for δD(CH4) measurements in (ice core) air. Pre-concentrated methane is focused in front of a high temperature oven (pre-pyrolysis trapping), and molecular hydrogen formed by pyrolysis is trapped afterwards (post-pyrolysis trapping), both on a carbon-PLOT capillary at −196 °C. Argon, oxygen, nitrogen, carbon monoxide, unpyrolysed methane and krypton are trapped together with H2 and must be separated using a second short, cooled chromatographic column to ensure accurate results. Pre- and post-pyrolysis trapping largely removes the isotopic fractionation induced during chromatographic separation and results in a narrow peak in the mass spectrometer. Air standards can be measured with a precision better than 1‰. For polar ice samples from glacial periods, we estimate a precision of 2.3‰ for 350 g of ice (or roughly 30 mL – at standard temperature and pressure (STP) – of air) with 350 ppb of methane. This corresponds to recent tropospheric air samples (about 1900 ppb CH4) of about 6 mL (STP) or about 500 pmol of pure CH4.